2019
DOI: 10.1155/2019/6318623
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Nano-TiO2/SiO2-Acrylic Composite Resin

Abstract: Waterborne acrylic resin is widely used as a binder of waterborne printing ink because of its excellent comprehensive properties. However, its further developments and applications are hindered by its poor UV resistance and water resistance. Therefore, an approach to prepare acrylic resin with excellent UV resistance and water resistance is described in this present study. The nano-TiO2/SiO2 composite particles were first modified with a silane coupling agent (KH-570) and a titanate coupling agent (NDZ-101) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The peak from 1100 cm-1could bean indication of the presence of asymmetric stretching vibrations of Si-O-Si bond as Du et al [44] explained. Moreover, in line with Quyen et al [20], the small peak observed at 940 cm-1 could be attributed to Ti-O-Si linkages a rming the bonding between Ti and Si At 1200°C.Thus, the Ti-O-Si bond would improve the thermal stability of TiO2 and suppress the phase transformation from anatase to rutile.…”
Section: Ii5 Characterization Of the Nanocompositesmentioning
confidence: 89%
“…The peak from 1100 cm-1could bean indication of the presence of asymmetric stretching vibrations of Si-O-Si bond as Du et al [44] explained. Moreover, in line with Quyen et al [20], the small peak observed at 940 cm-1 could be attributed to Ti-O-Si linkages a rming the bonding between Ti and Si At 1200°C.Thus, the Ti-O-Si bond would improve the thermal stability of TiO2 and suppress the phase transformation from anatase to rutile.…”
Section: Ii5 Characterization Of the Nanocompositesmentioning
confidence: 89%
“…Although the anti-corrosion performance was enhanced with the introduction of C 8 mimPF 6 , it was still inferior to other anti-corrosion coatings, such as epoxy, due to the poor performance of neat waterborne PMMA-co-PBA [ 3 ]. However, as one of the acrylate coatings, waterborne PMMA-co-PBA coatings have advantages such as low cost, excellent adhesion, coalescence, color retention, and satisfactory UV and hydrolysis resistance [ 4 , 5 ]. Rather than searching for alternative waterborne coating resins without prior anti-corrosion resistance to encapsulate C 8 mimPF 6 , direct addition of fillers to enhance the barrier effect of the neat PMMA-co-PBA coating is a facile route to improve the anti-corrosion performance [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The UV resistance, thermal stability, flexural strength, wettability, photocatalytic performance and cleanability of polymer based materials could be improved in the presence of TNP. [5][6][7][8][9][10][11][12] However, due to the large surface to volume ratio of TNP as well as the difference in the nature and structure between TNP and organic polymer, TNP tend to agglomerate easily to form bigger clusters in polymer matrix. Thus, it causes to decrease in some properties of the polymeric nanocomposite materials.…”
Section: Introductionmentioning
confidence: 99%